Pengaruh Penerapan Sistem E-Registration, E-Filing, Dan Transparansi Pajak Terhadap Kepatuhan Wajib Pajak Badan Dengan Sanksi Perpajakan Sebagai Variabel Moderasi (Studi Kasus Pada Wajib Pajak Badan Di Kpp Pratama Jakarta Cilandak) - Erwin Indriyanto; Siska Siska (Journal of Economic, Bussines and Accounting (COSTING), 2024)
By focusing on mandatory tax agencies at KPP Pratama Jakarta Cilandak, this study examines the impact of electronic registration systems, electronic reporting and tax transparency on compliance of mandatory tax agencies against tax sanctions. In addition, it also uses a purposive sampling method to issue questionnaires to taxpayer agencies to collect raw data to test moderator variables. The sample group consisted of 100 respondents who were taxpayers registered at KPP Pratama Jakarta Cilandak. The findings show that the application of an electronic registration system, electronic filing, and tax transparency has a positive and significant effect on corporate taxpayer compliance. Interestingly, tax sanctions do not actually amplify this effect Keywords : E-registrasi, E-filing, Tax Transparency, Taxpayer Compliance, and Tax Sanctions